Description of a Cairn in the Isle of Bute (Proceedings of the Society of Antiquaries of Scotland, 1862)
A report on the excavation of Cairnbaan in Bute, including its dimensions and the author's suggestions of what it may have been used for. He also quotes another antiquarian's investigation into the cairns at Kilfinan in Argyll. Meeting notes for 10 January, 1859 are appended.